2014
DOI: 10.3341/jkos.2014.55.9.1376
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Burn Caused by Carbon Dioxide Ultrapulsed Laser for Nevus Removal

Abstract: Purpose: Periocular carbon dioxide ultrapulsed laser surgery can induce ocular damage. Herein we report a rare case of corneal burn after carbon dioxide ultrapulsed laser for nevus removal. Case summary: A 25-year-old female patient presented with ocular pain, decreased visual acuity, and metamorphopsia in the left eye after laser surgery for nevus removal at a dermatology clinic 4 days prior. The patient's best corrected visual acuity in the left eye was 20/100. Central corneal haziness and corneal epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In addition to potentially causing ectropion of the eyelids, CO 2 lasers can injure the cornea, sclera, and lens. 16,54,55,63 The same potential injury pattern would be expected with the Er:YAG laser, although no published cases were found.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition to potentially causing ectropion of the eyelids, CO 2 lasers can injure the cornea, sclera, and lens. 16,54,55,63 The same potential injury pattern would be expected with the Er:YAG laser, although no published cases were found.…”
Section: Discussionmentioning
confidence: 78%
“…Our review identified 119 published case reports of ocular injury from lasers and IPL. 11,13,14,16,18–35 , 36–65 Fifty-nine of these cases resulted in a temporary (54 of 59) or permanent (5 of 59) ectropion after CO 2 laser resurfacing where the laser was directed at the eyelids. 13,14,63–65 A 1997 survey of American practitioners performing laser resurfacing found that ectropion occurs in 0.4% of cases.…”
Section: Resultsmentioning
confidence: 99%
“…This thermal complication either seems to be extremely rare or has been underreported in the literature as we found only five papers on this subject. In three, the authors described the thermal cause , one written in Korean , the third gave a 0.3% incidence of corneal injury after CO 2 laser blepharoplasty, however, without details. In the other two , we believe the cause was thermal but the authors proposed other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional carbon dioxide (CO 2 ) laser treatment has become a common procedure to treat various cutaneous conditions, including periocular rhytides. Sporadically, dermal side effects and complications occur whereas very few publications address ocular complications . We present a patient who was treated for periocular rhytides with a CO 2 laser.…”
Section: Introductionmentioning
confidence: 99%
“…Many blindness accidents have been reported from the use of lasers in this wavelength range. 7,8 The eye protection must block the light from the laser as much as possible.…”
Section: Introductionmentioning
confidence: 99%